The Study of Sound Intensity Distribution and Its Relationship Overtime with the Livelihoods of People in the Community Around Samui Airport - Sri-ta, Kodchagan; Thongyat, Kanokpim; Tosiri, Supawadee; Junkaew, Nutthapol (Journal of Applied Informatics and Technology, 2024)
The purpose of this study is to investigate the distribution of sound intensity and its relationship over time with the livelihoods of people in three communities surrounding Samui Airport, consisting of Ban Bang Rak, Ban Plai Laem, and Ban Chaweng. By utilizing geographic information systems (GIS) to perform spatial interpolation, the study found that the maximum sound intensity level during the morning period from 08:00 to 11:00 was 93.72 decibels. There are 4,650 households that have been impacted by noise levels exceeding 70 decibels. During the afternoon period from 13:00 to 16:00, the maximum sound level recorded was 88.69 decibels. There are 3,260 households impacted by noise levels exceeding 70 decibels. During the evening period from 18:00 to 21:00, the maximum sound level recorded was 86.06 decibels. There is a total of 4,957 households impacted by noise levels exceeding 70 decibels. In conclusion, the study revealed that the most significant impact of noise on the well-being of individuals in the neighborhoods surrounding Samui Airport occurs during the evening hours from 18:00 to 21:00. This observation corresponds with the survey findings. Because this timeframe coincides with peak flight activity and is also when individuals typically seek leisure and tranquillity, it is during the evening period that noise has the most significant impact on the community’s quality of life.